Miten Suomessa toimivat ulkomaiset yritykset eroavat suomalaisessa omistuksessa olevista yrityksistä? - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2012)
– We analyse foreign-owned companies operating in Finland and compare them with domestic non-multinational firms while controlling separately for domestic multinational firms. The statistical and micro-econometric analysis is done using Statistics Finland data that contain all firms with at least ten employees in 1998-2008, partly in 1995-2010. We also control for a number of exogenous factors. According to the results, foreign-owned firms have higher productivity than domestic non-multinational firms. There is no difference in the average growth rate of productivity if the difference in levels is not controlled. Accordingly, a shift to foreign ownership has, on average, not affected the growth rate of productivity. The results concerning the growth rate of employment depend upon the method and timespan used in the analysis. The personnel of foreign-owned firms have a longer and higher education than the personnel of domestic non-multinational firms. Foreign-owned firms pay more direct taxes in relation to the number of their employees, which is partly due to these firms' higher productivity. The probability of becoming a target of a foreign acquisition is higher for medium-sized and large Finnish firms with high productivity than other firms.
Keywords: C23; F23; G34; J24; 330; multinational firms; ownership change; productivity; employment; education; taxes